A regexcriteria API to complete the power of regular expressions engine - Boulchahoub Hassan; Rachiq Amina; Labriji Amine; Labriji Elhoussin; Mohamed Azouazi (Institute of Advanced Engineering and Science, 2019)
Regular expressions are heavily used in the field of computer programming. They are known by their strength to search or replace parts of strings according to a given structure (mails, phone, numbers, etc.). Currently regular expressions are only used to search for some patterns or to make some substitutions in strings. However, the need may be wider than that when it comes to order the results of a regular expression or to group them according to some criteria. Developers are always called to analyze the results of a regular expression by doing some restrictions such as (equal, not equal, between) or some projections like (maximum, average, grouping by ..) or sorts. Unfortunately, to do these treatments, the developer must implement his own algorithms which cost him a remarkable effort and a waste of time. We propose in this paper an API called RegexCriteria inspired from Hibernate Criteria to support developer while analysing the results of a regular expression.